Analisis Pengaruh Usia Terhadap Kemenangan Petarung Gladiator Dengan Metode Regresi Linier Sederhana - Maulana, Firdan (Jejaring Penelitian dan Pengabdian Masyarakat (JPPM), 2025)
Gladiators were fighters in ancient Rome who participated in arena battles as a form of public entertainment, often held in the Colosseum in Rome. The battles could take place between gladiators or against wild animals. Gladiators usually came from various backgrounds, such as prisoners of war, slaves, or even volunteers. The life of a gladiator was filled with risks, but those who survived could gain fame, wealth, and freedom. This study aims to analyze the effect of age on gladiator fighters' victories using a simple linear regression method, where the battle is influenced by various factors, including age. The data used includes the age and victories of gladiator fighters, which were analyzed to show a correlation between the gladiators' age and the number of victories obtained. This study provides specific insights into the physical characteristics that affect success in battle, as well as offering scientific factors for researchers regarding factors that influence fighting performance.